MANAJEMEN PEMBELAJARAN KETERAMPILAN ANAK TUNAGRAHITA DI SEKOLAH LUAR BIASA (SLB) C WIYATA DHARMA 2 SLEMAN TAHUN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The Management of Skill learning of Mental Disable Children at Wiyata Dharma 2 Special Education, Sleman, Year 2012/2013 The goal of The Research was to describe The Management of skill learning, supporting factor and how to empower the implementation of skill and also obstacle factor, and effort to overcome the obstacle factor of skill learning at Wiyata Dharma 2 SpecialEducation, Sleman, Yogyakarta year 2012/2013. The Research used qualitative approach, data source from informants include: Headmaster, the vice principle student, the vice principal infrastructure, the vice principal staff, Skill Teacher, parental, Committee and class teachers. The collection of data were applied observation, interview and document. The validation of data was done by lengthening the participation, perseverance of observation and triangulation. The Result of the Research showed that the skill learning at Wiyata Dharma 2 Special Education went well. The evaluation result of input showed that the educator is adequate, the expert is inadequate, the infrastructure is adequate, the Management of Fund from any source is good enough, learning Resources is not complete and is not maximal in the use of it. The evaluation result of process showed that organization of skill activities program is good enough, and process of skill learning that include learning process, studentâ€™s interaction and implementation skill practice Activities are good. The internal supporting factors such as a sense of fun and spirit of the students, and External are complete infrastructure and school fund for the material and a cooperative as means of promotion. The internal obstacle are the low ability of the student and easy to strike, and the external factors are not all the teachers teach according to their education, lack ofsupport and Cooperation of parents, lack of businesses receiving the works and hire the students. Effort to overcome the obstacle factor are arrange a â€œmotivation apelâ€ every day, improve collaboration with parental and society support. The conclusion of this Research is management of skill learning at Wiyata Dharma 2 Special Education went well, structure of the Management is structured and well done. Based on those is recommended to fulfill the expert of skill so the skill that they learned is optimal.